Partisipasi Masyarakat Dalam Program Bangkit Berdaya di Kecamatan Telanaipura Kota Jambi - Putra, Dima Pratama; Jeddawi , Murtir; Masrich, Andi (UIR Press, 2024)
Bangkit Berdaya is a program that aims to encourage the accelerated development of neighborhood infrastructure and utilities (RT) in the Jambi City area, as well as encouraging community participation in environmental development. This research was motivated by the research author's interest in the participation of the people of Telanaipura District, Jambi City in the development of infrastructure in the sub-district environment. This research aims to find out how community participation in the rise to empowerment program and determine the factors inhibiting community participation in the rise to empowerment program as well as efforts to overcome the factors inhibiting community participation in the rise to empowerment program in the Telanaipura subdistrict, Jambi City. The theory used is participation theory according to (Eko, 2004:222). The method used in this research is a qualitative research method using a descriptive approach which is intended to understand situations, events, roles, groups or social interactions. Data obtained through literature study, observation, interview documentation. The results of the research show that firstly, the Community Voice which conveys aspirations, ideas, needs, interests and so on through discussion forums in neighborhood units (RT) in sub-districts within the Telanaipura sub-district, Jambi City has been running well. The next access is an arena of meeting point between the community and the government. The government is obliged to open access for the community and provide public services or provide other public infrastructure for the community. There are still sub-districts where community participation in the implementation of the rise to power program has not run optimally. The final control is the community's ability to critically assess policies, both the government and their own community, which have not yet been implemented well.